2002
DOI: 10.1046/j.1526-4610.42.s2.4.x
|View full text |Cite
|
Sign up to set email alerts
|

Frovatriptan: A Review of Drug‐Drug Interactions

Abstract: Because it has no inhibitory or inducing effect on CYP isoenzymes and is only slightly bound to plasma proteins, it is unlikely that frovatriptan will alter the pharmacokinetics of concomitantly administered drugs. Frovatriptan, therefore, appears to have a low risk of interaction with other drugs, and adjustments of dose are unlikely to be required when it is coadministered with other agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
5
26
0
1
Order By: Relevance
“…Sumatriptan has a relatively low oral bioavailability and a short half-life (Perry and Markham 1998). In contrast, newer triptans such as almotriptan, naratriptan, frovatriptan, rizatriptan, zolmitriptan and eletriptan exhibit enhanced pharmacokinetic characteristics compared with sumatriptan including rapid attainment of therapeutic plasma levels, greater oral bioavailability and greater ability to cross the blood-brain barrier (Seaber et al 1998;Mathew 1999;Vyas et al 2000;Buchan et al 2002;Jansat et al 2002;Milton et al 2002;Yates et al 2002;Evans et al 2003). The excretion of frovatriptan is mainly renal, as well as that of naratriptan that also undergoes CYP450-mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Sumatriptan has a relatively low oral bioavailability and a short half-life (Perry and Markham 1998). In contrast, newer triptans such as almotriptan, naratriptan, frovatriptan, rizatriptan, zolmitriptan and eletriptan exhibit enhanced pharmacokinetic characteristics compared with sumatriptan including rapid attainment of therapeutic plasma levels, greater oral bioavailability and greater ability to cross the blood-brain barrier (Seaber et al 1998;Mathew 1999;Vyas et al 2000;Buchan et al 2002;Jansat et al 2002;Milton et al 2002;Yates et al 2002;Evans et al 2003). The excretion of frovatriptan is mainly renal, as well as that of naratriptan that also undergoes CYP450-mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…When frovatriptan was taken together with an oral contraceptive, there were slight increases in the maximum concentrations of frovatriptan; however, these findings were considered to have no clinical significance. 78 Likewise, when sumatriptan was administered concomitantly with oral contraceptives, there were no clinically relevant changes in the plasma concentrations of any of the medications compared with when they were administered alone. 79 Although 34% of women taking eletriptan in a large comprehensive review 23 were also taking oral contraceptives or hormone replacement therapy, there were no clinically important differences in the incidence of adverse events or the rate of discontinuations due to adverse events when eletriptan was used together with oral contraceptives or hormone replacement therapy.…”
Section: Metabolic Pathways and Drug-drug Interactionsmentioning
confidence: 94%
“…28 Frovatriptan has distinctive pharmacokinetic and pharmacological properties, and was developed to offer a long duration of action and low likelihood of drug interactions and side effects. [29][30][31] It is more selective for cerebral arteries compared with coronary arteries and is thus more suitable for treating those at risk from coronary artery disease. Although frovatriptan is mainly metabolised by cytochrome P450 (CYP) 1A2 it does not affect (inhibit or induce) this or other CYP isoenzymes.…”
Section: Frovatriptanmentioning
confidence: 99%
“…It also is not a substrate for monoamine oxidase-A in contrast to some other triptans and does not bind to plasma proteins to a large extent, hence it has a low risk of pharmacokinetic drug interactions. 31 Results from three randomised, placebo-controlled, double-blind, parallel-group trials (2,676 migraine patients) indicated that headache response after 2 hours was significantly greater with frovatriptan compared with placebo (p≤0.001) and was also approximately twice as effective at 4 hours. 32 Furthermore, in most patients, time to headache response was within 1.5 hours and there was a low incidence (10-25%) of 24-hour headache recurrence.…”
Section: Frovatriptanmentioning
confidence: 99%